Improving Product Quality and Meg Recovery Unit (Mru) Efficiency by Applying Lean Six Sigma Methods in A Floating Production Unit - Joko Santoso; Ariska Dithya Pratiwi; Ardhianiswari Diah Ekawati (Syntax Literate, 2022)
One of the challenges of managing gas from deep-water wells is ensuring that the flow from the subsea does not form a hydrate, which causes the production to stop due to blockage in the pipeline. Injection Mono Ethylene Glycol (MEG) is the technology used to prevent hydrates formation. The MEG Recovery Unit (MRU) is a system used to recover rich MEG from wells. However, after operating for four years, the MRU experienced a decrease in performance as indicated by lean MEG products that did not meet the specifications, and MEG losses exceeded the specified limit. This study examines the case by taking an effective approach to solving problems by applying the Lean Six Sigma method that focuses on improving product quality and MRU efficiency using Define-Measure-Analyze-Improve-Control (DMAIC) framework. The process starts by defining the problem of the MRU system with involves brainstorming consultation to select the root cause of the problem. Classifying and assessing these reasons has been done through the use of various tools, the fishbone diagram, Failure Mode and Effect Analysis (FMEA), and the 5 why analysis. The results show that Lean Six Sigma methodologies and tools effectively find the root causes of problems accurately and can provide continuous improvement. The quality of lean MEG products has increased with the cleanliness value below NAS 8 and Total Dissolve Solid below 100 ppm. This reduces operating costs to replace filters with savings of $42,000 per month. Meanwhile, MRU efficiency increased from 96% to 98%, and MEG losses reduced from 1500 liters/day to 750 liters/day equivalent to a savings of $36,000 per month